Ageism in Job-Seeking and Recruitment Practices: A Systematic Literature Review - Oudomvilay, Thanakone (Auckland University of Technology, 2024)
Despite a wealth of experience across generations, ageism remains a persistent barrier in job seeking. The global trend of an aging population has created a unique workforce with up to five generations, from Traditionalists to Generation Z. Nevertheless, both older workers and younger workers face persistent ageism in the workplace. As a result, ageism in recruitment and its mitigation has become an emerging issue for scholars and practitioners. While existing studies provide valuable insights, the current body of knowledge remains fragmented. This paper addresses two key research questions: 1) what is known from the literature on the challenges of ageism experienced by different age groups in job seeking? and 2) how do employers account for age diversity in recruitment practices? In addition, it aims to analyse and synthesise the findings from the literature to identify themes, knowledge gaps and recommendations for future research and practices. Six key themes were identified through the analysis of 27 studies: 1) ageism in stages of recruitment, 2) ageist stereotypes, 3) intersectional impacts of ageism, 4) age cues and physical appearance in ageism, 5) reverse ageism in recruitment, 6) ageism mitigation intervention. This paper contributes to the theoretical understanding of ageism within the specific context of recruitment and its parallels with intersectionality, internalised ageism, the negative discourse of aging and social theories. Furthermore, the paper also highlights age-diversity approaches to mitigate ageism in recruitment practices. Lastly, it identifies the key areas for future research to empirically identify and evaluate ageism mitigation interventions across diverse contexts.